2013
DOI: 10.1073/pnas.1212471110
|View full text |Cite
|
Sign up to set email alerts
|

Using data to attribute episodes of warming and cooling in instrumental records

Abstract: The observed global-warming rate has been nonuniform, and the cause of each episode of slowing in the expected warming rate is the subject of intense debate. To explain this, nonrecurrent events have commonly been invoked for each episode separately. After reviewing evidence in both the latest global data (HadCRUT4) and the longest instrumental record, Central England Temperature, a revised picture is emerging that gives a consistent attribution for each multidecadal episode of warming and cooling in recent hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
109
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 53 publications
13
109
3
Order By: Relevance
“…This natural multidecadal oscillation, superimposed on a secular warming trend, is proposed for explaining the non-monotonic warming shown by global temperatures during the 20th century, including the cooling of the mid-century and the recent slowdown in the warming. The authors argue that the warming trend has remained almost constant since 1910 at 0.07-0.08 °C/decade 48 . The most significant differences between the results from these papers and those presented here can be attributed to the use of a linear trend to represent the warming trend, as well as to the lack of testing for breaks in the trend function.…”
Section: S8 Relation To Previous Results In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This natural multidecadal oscillation, superimposed on a secular warming trend, is proposed for explaining the non-monotonic warming shown by global temperatures during the 20th century, including the cooling of the mid-century and the recent slowdown in the warming. The authors argue that the warming trend has remained almost constant since 1910 at 0.07-0.08 °C/decade 48 . The most significant differences between the results from these papers and those presented here can be attributed to the use of a linear trend to represent the warming trend, as well as to the lack of testing for breaks in the trend function.…”
Section: S8 Relation To Previous Results In the Literaturementioning
confidence: 99%
“…Two recent papers 48,49 are related to the present study, in the sense that they use a similar regression-based approach to filter the effects of AMO from global temperatures in order to extract a clearer warming signal from the data. Nevertheless, the estimates and interpretation of the warming trend and of its nonlinearities are very different to those presented here.…”
Section: S8 Relation To Previous Results In the Literaturementioning
confidence: 99%
“…Semenov et al (2010) estimated the AMO contribution to post 1970 global warming to be 0.24°C. Tung and Zhou (2013) found that neglecting the AMO leads to an overestimation of the global mean anthropogenic warming trend during the second half of the twentieth century by about a factor of two. Hansen et al (http://www.columbia.edu/*jeh1/mailings/ 2013/20130115_Temperature2012.pdf) suggested that natural variability is responsible for over a decade of stable global mean temperatures since about 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The global climate change is driven by increasing atmospheric concentration of greenhouse gases (GHGs) as well as by natural climate variability (Wu et al 2007(Wu et al , 2011aTung and Zhou 2013). While the warming by increasing GHGs is well captured by climate models (Solomon et al 2007), the treatment of natural variability remains a challenge (Dai et al 2005;Zhang et al 2007;Solomon et al 2011;Wyatt et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Observations and model simulations over recent centuries suggested that multidecadal to multicentennial cyclic change of solar activity and climate patterns (such as Pacific Decadal Oscillation, Atlantic Multidecadal Oscillation, and North Atlantic Deep Water) still existed under anthropogenic forcing and played an important role in regulating global to regional terrestrial (EA, North America, and Europe) and marine (North Atlantic and Pacific) climate change during the past centuries [9][10][11][12][13][14][15] . But recent studies based on global and regional climate records indicated that the warming of the past century is unprecedented and not relative to natural forcing but anthropogenic forcing 4,16,17 .…”
mentioning
confidence: 99%